"012012 or 111000": preference for consumption pattern-seeking. (29th June 2020) - Kim, Jungkeun; Cui, Yuanyuan (Gina); Hwang, Euejung; Franklin, Drew; Seo, Yuri
Abstract : Purpose: This paper aims to examine how consumers make choices when they are faced with a fixed set of available options, consisting of both preferred and less-preferred choices, in the domain of food consumption. Specifically, the paper offers a novel perspective to predict repeated choice decisions in food consumption, which is termed as "pattern-seeking" – a consumption choice pattern that involves a coherent repetitive sequence of sub-groupings or coherently concentrated sub-groupings of options. Design/methodology/approach: Eight experimental studies that contrast the existing theoretical predictions regarding repeated choices (e.g. primacy effect, recency effect, variety vs consistency) against pattern-seeking were conducted using hypothetical and actual food choices. Findings: The results of experimental studies show that an explicit decision pattern (i.e. pattern-seeking) emerges as the most significant predictor of repeated choice in the food consumption domain. Research limitations/implications: This study offers a novel perspective on how consumers make repeated choices in the domain of food consumption. Practical implications: The results show that consumers prefer food consumption with a pattern (vs non-pattern). Thus, it would be better to generate marketing activities that allow customers to satisfy their pattern-seeking more easily. Originality/value: This study advances the literature on repeated food choices by demonstrating that people possess an inherent preference for patterns in food consumption.